Plasmin Promotes Keratinocyte Migration and Phagocytic-killing Accompanied by Suppression of Cell Proliferation which may Facilitate Re-epithelialization of Wound Beds. Issue 3 (2004) - Szabo, Imre; Simon, Miklos; Hunyadi, Janos
Abstract : Abstract Keratinocytes were shown to induce the activation of plasminogen activator resulting in the formation of plasmin and the initiation of proteolysis in vitro . Activation of surface bound plasminogen may localize protease activity in the pericellular microenvironment and play a role in inducing both a conformational change and cell locomotion. Plasmin, however, can induce non-proteolytic effects on certain cell functions in a variety of cell lineages. In the present study we examined the effects of plasmin on keratinocytes with a focus on its role in the process of re-epithelialization, which included studies of cell migration, phagocytic-killing and cell proliferation. Migration of freshly isolated human epidermal keratinocytes was analyzed utilizing the agarose gel assay in the presence of 10% human serum. Plasmin at the concentration of 25 U/l induced a 160% increase in the chemotactic migration of keratinocytes that was completely blocked by the plasmin inhibitor α2 -antiplasmin (Serpin). In the absence of serum, plasmin also induced a reversible chemotactic migration of HaCaT keratinocytes as determined utilizing the microchemotaxis assay. Dose-response analysis showed a bi-phasic effect of plasmin with a maximum increase of 52% in keratinocyte chemotaxis at a concentration of 25 U/l. HaCaT cells on the other hand, showed no detectable in vitro chemokinesis by plasmin. Phagocytic-killing of Candida albicans by freshly isolated epidermal keratinocytes was enhanced in the presence of 25 U/l plasmin which was also reversible by the addition of Serpin. Spontaneous proliferation of HaCaT keratinocytes as determined by 3 H-Thymidine uptake on the other hand, was reduced by 47 and 13% in cultures with 25 U/l plasmin for 24 and 48 h respectively, in a Serpin reversible manner. These data suggest that plasmin-induced chemotactic migration of epidermal keratinocytes is accompanied by enhanced phagocytic-killing coupled with suppression of proliferation of these cells which may facilitate re-epithelialization following skin injury.